DESIGN OF E-PSYCOTES INFORMATION SYSTEM USING PHP AND MYSQL IN PT. INFOMEDIA HUMANIKA BANDUNG - Roni Surahman (INFOKOM (Informatika & Komputer), 2018)
This study aims to analyze, design and build psychotes information systems at PT Infomedia Humanika Bandung so that the process of taking data psychotes can be faster, accurate and efficient.Data collection methods was using observation, intervie and literature study, while the method of this information system design was using objectoriented approach with UML modeling (Unified Modeling Language).Software development method using prototype method, whichis implemented with PHP programming language and MySQL as database. The main problem is the length of the scanning process due to the large number of data and inconsistencies in the procedure of charging test answers, the inefficiency in recording the data because it must be input into Microsoft Excel application. To overcome these problems then made e-psychotes information system with software testing methods blackbox method. The suggestions given is: Performing system maintenance regularly, doing system development, Held training for User and Admin about system usage procedure.